2017
DOI: 10.1155/2017/4260702
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Nebulization of Ropivacaine during Laparoscopic Cholecystectomy: Dose Finding and Pharmacokinetic Study

Abstract: Background. Intraperitoneal nebulization of ropivacaine reduces postoperative pain and morphine consumption after laparoscopic surgery. The aim of this multicenter double-blind randomized controlled trial was to assess the efficacy of different doses and dose-related absorption of ropivacaine when nebulized in the peritoneal cavity during laparoscopic cholecystectomy. Methods. Patients were randomized to receive 50, 100, or 150 mg of ropivacaine 1% by peritoneal nebulization through a nebulizer. Morphine consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In our study, we used ropivacaine for intraperitoneal nebulization as it is associated with less toxicity and is equally effective as bupivacaine. In a dose-finding study by Allegri et al [ 12 ] 50 mg of nebulized ropivacaine was found to be effective in providing adequate analgesia in patients undergoing laparoscopic cholecystectomy. Further increase in the dose of ropivacaine did not provide any additional benefit.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used ropivacaine for intraperitoneal nebulization as it is associated with less toxicity and is equally effective as bupivacaine. In a dose-finding study by Allegri et al [ 12 ] 50 mg of nebulized ropivacaine was found to be effective in providing adequate analgesia in patients undergoing laparoscopic cholecystectomy. Further increase in the dose of ropivacaine did not provide any additional benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma concentration remained consistent under the mean toxic plasma concentration. They also found that increasing the dose of ropivacaine from 50 mg to 150 mg did not reduce postoperative pain intensity, morphine consumption, incidence of PONV, or readiness for discharge, but was instead associated with the incidence of postoperative shivering [23].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration (0.5%) and volume (20 ml) of ropivacaine in the instillation group was based on standard practice, and the lower volume (10 ml) and higher concentration (1%) of ropivacaine in the nebulization group was based on nebulization time (the Aeroneb Pro Ⓡ device can deliver 5 ml of solution in 5–8 min). Moreover, a recent study showed that increasing the dose of ropivacaine from 50 mg to 150 mg did not show any clinical benefit [23].…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies conducted on the effectiveness of intraperitoneal local anesthetic in laparoscopic procedures including bariatric surgery. However, results from such studies are inconclusive; some demonstrated a reduction in post-operative pain [ 8 , 10 , 12 – 15 , 18 , 19 ] yet others found no difference [ 9 , 11 , 16 , 17 ]. Previous studies conducted on intraperitoneal local anesthetic in bariatric patients have administered a standardized volume of local anesthetic to every patient.…”
Section: Introductionmentioning
confidence: 99%